State-building in Afghanistan? Taking stock of the international presence in the Hindu Kush - Boris Wilke (Stiftung Wissenschaft und Politik (SWP), 2004)
This study argues for concentrating the international community's involvement on a few achievable goals: * The structure of the international intervention should be more closely tailored to strategic goals. At the top of the list should be the creation of state structures (state-building). Longer-term nation-building goals should be left to the actors in the region. * Despite the minimization of the United Nations' involvement in Afghanistan ("light footprint" approach), there are now parallel lines of authority at all levels. In the medium term at least they weaken the central state and contradict the goal of state-building, so they must be dismantled wherever possible. * Nevertheless, the international community will need staying power. For decades, the shape and structure of the Afghan buffer state has been determined by the international system, while most Afghans managed without a state. There is no reason to assume that this historical rule will cease to apply precisely at a time when statehood is coming under pressure almost everywhere. Establishing functioning statehood in Afghanistan means assuming a significant portion of the responsibility and costs involved. * Existing instruments do not take sufficient account of the transnational character of the causes of conflict. These cannot be effectively counteracted through a country-specific approach to security and development. Forming a regional security community would also fit in with the limited nature of the international community's political, financial, and military involvement. (SWP-Research Papers / SWP)
Keywords: 320